Therapeutic Trials in Human Transmissible Spongiform Encephalopathies: Recent Advances and Problems to Address - Zerr, Inga (Infectious Disorders - Drug Targets, 2009)
The progress in understanding disease pathology and phenomenology in prion disorders and recent advances in diagnostic techniques might allow researchers to think about therapeutic trials in CJD patients. Some attempts have been made in the past. Drugs tested involved a variety of compounds, which belong to antimicrobial, antiinflammatory or analgesic substance classes. Most papers on this subject describe single case reports. Controlled trials are virtually not available and a double-blinded study was published for flupirtine only. Despite it has been demonstrated that a clinical trial is feasible, the clinicians might face several specific problems when evaluating the efficacy of the drug in CJD, such as rareness of the disease, lack of appropriate preclinical test and heterogeneous clinical presentation in humans. These problems have to be carefully addressed in future trials.
Keywords: Prion